TPU-based composite material as well as preparation method and application thereof
By adopting temperature-raising dyeing treatment, acid bath treatment and surface hydrophobic treatment in TPU matrix composite materials, the problem of difficulty in uniform dispersing and firmly bonding of nanoconductive materials in TPU is solved, and the good conductivity and multiple properties of the material are achieved, which is suitable for wearable electronic devices.
Patent Information
- Application Number
- CN202411669741.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Among existing TPU-based composite materials, nanoconductive materials (nCMs) are difficult to disperse and firmly combine uniformly, resulting in inconsistent conductivity, affecting mechanical properties and sensing properties, and cannot meet the needs of wearable electronic devices.
By mixing the dispersion of nanoconductive material with the TPU parts, using temperature-raising dyeing treatment, acid bath treatment and surface hydrophobic treatment, the nCMs are uniformly dispersed and firmly bonded in the TPU, and a hydrophobic film is formed on the surface.
It realizes good conductivity of TPU-based composite materials, taking into account mechanical properties, sensing properties and hydrophobic properties, making them suitable for wearable electronic devices.
Smart Images

Figure CN119570230A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and specifically relates to a TPU-based composite material and a preparation method and application thereof. Background Art
[0002] Thermoplastic polyurethane elastomer, also known as thermoplastic polyurethane rubber (TPU), has both the high elasticity of rubber and the rigidity of plastic. It can be melt processed and is suitable for high-precision and high-resolution printing. 3D printed TPU parts have good wear resistance, weather resistance, tensile strength, and hardness range, and are widely used in design, footwear, clothing, biomedicine, and automotive fields.
[0003] Nanomaterials have attracted much attention in the field of composite materials technology due to their special physical and chemical properties such as optical properties, chemical reactivity, magnetism, superconductivity and plastic deformation. In recent years, a type of nanomaterial, MXene, has attracted particular attention. MXene materials refer to two-dimensional layered materials derived from transition metal carbon / nitrogen / carbonitrides (such as Ti3C2). MXene, carbon nanotubes (CNTs) and graphene (Gr) are combined with other materials as nanoconductive materials (nCMs) to obtain composite materials with significantly improved electrical conductivity, thermal conductivity and electromagnetic shielding performance. The above composite materials are widely used in the field of wearable devices after the surface is hydrophobicized.
[0004] At present, there are two methods for the composite of nCMs and TPU. Method 1 is to mix nCMs and TPU matrix materials in a certain proportion, add necessary additives, and prepare composite materials by melt blending; Method 2 is to coat nCMs on the surface of 3D printed TPU parts by spraying, dipping or electrochemical deposition, and further dry to obtain the finished product. The two interact in different ways. In the former, nCMs are easy to agglomerate, and it is difficult for nCMs to disperse evenly during melt blending. During the printing process, not only does it lead to inconsistent conductive properties of the finished product, but it also affects the interlayer adhesion of 3D printed parts; in the latter, for molded TPU parts, it is easier to achieve conductive composites with complex shapes and structures. At the same time, the post-processing process of composite nCMs is relatively simple, which can be completed through steps such as cleaning and curing, but the bonding strength of nCMs on the surface of TPU parts is low. It affects the comprehensive performance of the composite material and cannot meet actual needs.
[0005] CN107523040A discloses a low-hardness, high-resilience, conductive TPU material, and its preparation method includes the following steps: (1) polymer polyol, polyisocyanate, chain extender / crosslinking agent, antistatic agent, and catalyst are mixed at 100-120°C, reacted for 1-2 hours, and then cured at 150-160°C to obtain material A; (2) polyester polyurethane material B is taken, material A, material B, and conductive material are extruded, and the material is softened at 150-180°C to obtain a low-hardness, high-resilience, conductive TPU material. The multifunctional TPU material of the invention has the properties of low hardness and high resilience, but because nCMs cannot be evenly dispersed and the internal bonding strength of the TPU parts is not enough, its conductive properties and mechanical properties will be affected to a certain extent, and it may not be applied to wearable electronic devices, health monitoring equipment, and sports monitoring equipment. TPU material, without adding any nCMs, has strong internal bonding strength but poor conductivity and sensing performance, which limits its application in wearable fields and other fields; therefore, how to develop a TPU-based composite material that can achieve uniform dispersion of nCMs in TPU and firm bonding with TPU, so that it has good conductivity while taking into account mechanical properties, sensing properties and hydrophobic properties, and is applied to wearable electronic devices and other fields has become an urgent problem to be solved. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to develop a TPU-based composite material and a preparation method thereof, so as to achieve uniform dispersion of nCMs in TPU and firm bonding with TPU, so that the TPU-based composite material has good conductive properties while taking into account mechanical properties, sensing properties and hydrophobic properties, and is applied to the field of wearable electronic devices.
[0007] In one aspect, the present invention provides a method for preparing a TPU-based composite material. The method comprises: mixing a dispersion containing a nano-conductive material with a TPU product, subjecting the mixture to a temperature-raising dyeing treatment, an acid bath treatment, and a surface hydrophobic treatment to obtain the TPU-based composite material;
[0008] The temperature-raising dyeing treatment is from room temperature to 80° C. to 95° C., the heating rate is 1.5 to 2° C. / min, and the heat preservation time is 40 to 60 minutes.
[0009] Furthermore, in the preparation method of the TPU-based composite material, the nano-conductive material is a mixture of one or more of carbon nanotubes, graphene, and Mxene.
[0010] Furthermore, TPU was used as raw material and TPU parts were prepared by fused deposition modeling 3D printing technology.
[0011] Furthermore, the added amount of the nano-conductive material is 2% to 10% of the mass of the TPU component.
[0012] Furthermore, ultrasound and mechanical stirring are used to optimize the dispersibility of the dispersion, the ultrasonic dispersion power is 300W to 500W, and the time is 30min to 60min; the mechanical stirring speed is 100rpm / min to 500rpm / min, and the time is 10min to 30min.
[0013] Furthermore, raw materials such as C6H8O7, Zr(SO4)2, Al2(SO4)3, FeCl3, Ce2(SO4)3, LaCl3, and deionized water were added to prepare acid baths with different pH values, and the transition metal ion Zr was introduced. 4+ 、Al 3+ , Fe 3+ Or rare earth metal ion Ce 3+ ,La 3+ Coordinate to "bridge" nCMs and TPU parts, further enhance the conductivity and improve the bonding strength between nCMs and TPU parts.
[0014] Furthermore, in order to improve the hydrophobicity of the surface of the TPU composite material, the surface of the TPU composite material is treated to be hydrophobic by using polydimethylsiloxane-modified polyurethane or hydroxyl-terminated polydimethylsiloxane-modified polyurethane or a mixture of polydimethylsiloxane-modified polyurethane and hydroxyl-terminated polydimethylsiloxane-modified polyurethane.
[0015] Furthermore, the concentration of the hydrophobic treatment material is 2% to 5% by mass.
[0016] On the other hand, the TPU-based composite material prepared by the above method has good electrical conductivity while taking into account mechanical properties and hydrophobic properties, and is used to prepare wearable electronic devices.
[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0018] The present invention overcomes the defects of the prior art. By utilizing a temperature-raising dyeing process, nCMs and TPU are compounded so that nCMs are evenly distributed in TPU and firmly bonded thereto, and metal ions are further introduced to improve the conductivity of the TPU-based composite material. A hydrophobic treatment is then performed on the surface of the composite material to form a uniform hydrophobic film on the surface to prepare a TPU-based composite material. The TPU-based composite material has better conductivity and takes into account mechanical properties, sensing properties and hydrophobic properties, so that it can be applied to wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 These are the strain tensile image and resistivity image of the intermediate product CNTs-COOH / TPU of Example 1.
[0021] Figure 2 These are the strain tensile image and resistivity image of the intermediate product CNTs-COOH / TPU of Example 2.
[0022] Figure 3 These are the strain tensile image and resistivity image of the intermediate product CNTs-COOH / TPU of Example 3.
[0023] Figure 4 This is an ultra-depth microscope image of the intermediate product CNTs-COOH / TPU in Example 6.
[0024] Figure 5 These are scanning electron microscope images of 3D printed TPU parts at different magnifications.
[0025] Figure 6 These are scanning electron microscope images of Zr / CNTs-COOH / TPU of Example 6 at different magnifications.
[0026] Figure 7 These are the strain tensile image and resistivity image of Zr / CNTs-COOH / TPU of Example 5.
[0027] Figure 8 These are the sensing images of the intermediate products CNTs-COOH / TPU and Zr / CNTs-COOH / TPU of Example 6.
[0028] Fig. 9 : is a test image of the water contact angle of the TPU-based composite material prepared in Example 6. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in the examples are conventional methods unless otherwise specified.
[0030] TPU: TUP powder was purchased from Yuksler Plastic Products Co., Ltd. with an average particle size of 50 μm to 80 μm.
[0031] The polydimethylsiloxane-modified polyurethane and the hydroxyl-terminated polydimethylsiloxane-modified polyurethane were homemade in the laboratory, and the preparation process was as follows: 9g IPDI, 10g PTMG, and 2.3g PDMS were weighed and added into a 250mL three-necked flask in sequence, and then DBTDL was added, and the mixture was heated to 80°C under oil bath conditions at a stirring speed of 200rpm and reacted for 3h. When the temperature dropped to 70°C, 1g DMPA was added for chain extension and reacted for 2h. 0.5g BDO was added, and the temperature was raised to 80°C for chain extension again and reacted for 1h. The oil bath heating was stopped, and the mixture was cooled to 40°C. 0.8g TEA was added and the neutralization reaction was carried out for 30min. 60g deionized water was added to the reaction mixture and the mixture was reacted for 30min at a stirring speed of 2000rpm. The reaction was terminated to obtain a modified polyurethane emulsion.
[0032] Example 1
[0033] This example provides a TPU-based composite material and a preparation method thereof.
[0034] The materials used in this embodiment are TPU, CNTs, H2SO4, HNO3, C6H8O7, Zr(SO4)2, and deionized water.
[0035] Step 1: Prepare TPU parts.
[0036] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0037] Step 2: Prepare CNTs-COOH dispersion,
[0038] (1) Using CNTs as raw materials, placing CNTs in a ball mill and milling them at a speed of 200 pm / min for 60 min;
[0039] (2) H2SO4 and HNO3 were mixed in a volume ratio of 3:1, and CNTs were dispersed in the acid mixed solution, and ultrasonic dispersion was performed at a power of 300 W for 60 min, and mechanical stirring was performed at a speed of 300 rpm / min at room temperature for 20 min to obtain a CNTs mixed solution;
[0040] (3) taking the CNTs mixed solution and filtering it, washing the filtered product with deionized water three times, and drying it in a vacuum oven at 60° C. for 12 h to obtain CNTs-COOH;
[0041] (4) Take CNTs-COOH, add deionized water, prepare a CNTs-COOH solution with a solid content of 10%, and perform ultrasonic dispersion treatment at a power of 300 W for 60 minutes to obtain a CNTs-COOH dispersion.
[0042] Step 3: Preparation of CNTs-COOH / TPU,
[0043] (1) diluting the solid content of the CNTs-COOH dispersion to 1%, taking 8% of the mass of the TPU product, ultrasonically dispersing at a power of 300 W for 30 min, and mechanically stirring at a speed of 300 rpm / min for 20 min;
[0044] (2) A gradient heating low-temperature dyeing process was adopted with the following process conditions: bath ratio 1:20, heating rate 2°C / min, the temperature was raised from room temperature to 80°C, 85°C, 90°C, and 95°C, respectively, and the temperature was kept at 80°C, 85°C, 90°C, and 95°C for 40 min. The CNTs-COOH and TPU parts were compounded by an infrared dyeing machine, washed with water, and dried in a convection oven for 12 h to prepare a CNTs-COOH / TPU composite material.
[0045] The strain tensile image and resistivity image of the CNTs-COOH / TPU composite material prepared in this example are as follows: Figure 1 shown.
[0046] Step 4: Preparation of Zr / CNTs-COOH / TPU,
[0047] Add 2g C6H8O7, 50mL deionized water, and 0.6% Zr(SO4)2 by mass of TPU to prepare an acid bath with a pH value of 2.5. Add the CNTs-COOH / TPU composite material to the Zr(SO4)2 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to prepare the Zr / CNTs-COOH / TPU composite material.
[0048] Step 5: Surface hydrophobicity treatment of Zr / CNTs-COOH / TPU composite material.
[0049] The concentration of the PDMS-modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, and the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties, thereby obtaining a TPU-based composite material.
[0050] Example 2
[0051] This example provides a conventional method for preparing a TPU-based composite material that is different from the preparation method of the present invention.
[0052] The materials used in this embodiment are TPU, CNTs, H2SO4, HNO3, C6H8O7, Zr(SO4)2, and deionized water.
[0053] Step 1: Prepare TPU parts.
[0054] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0055] Step 2: Prepare CNTs-COOH dispersion,
[0056] (1) Using CNTs as raw materials, placing CNTs in a ball mill and milling them at a speed of 200 pm / min for 60 min;
[0057] (2) H2SO4 and HNO3 were mixed in a volume ratio of 3:1, and CNTs were dispersed in the acid mixed solution, and ultrasonic dispersion was performed at a power of 300 W for 60 min, and mechanical stirring was performed at a speed of 300 rpm / min at room temperature for 20 min to obtain a CNTs mixed solution;
[0058] (3) taking the CNTs mixed solution and filtering it, washing the filtered product with deionized water three times, and drying it in a vacuum oven at 60° C. for 12 h to obtain CNTs-COOH;
[0059] (4) Take CNTs-COOH, add deionized water, prepare a CNTs-COOH solution with a solid content of 10%, and perform ultrasonic dispersion treatment at a power of 300 W for 60 minutes to obtain a CNTs-COOH dispersion.
[0060] Step 3: Preparation of CNTs-COOH / TPU,
[0061] (1) Diluting the solid content of the CNTs-COOH dispersion to 1%, taking 2%, 4%, 6%, 8%, and 10% of the mass of the TPU product, respectively, ultrasonically dispersed at a power of 300 W for 30 min, and mechanically stirred at a speed of 300 rpm / min for 20 min;
[0062] (2) The 3D printed TPU parts were immersed in the CNTs-COOH dispersion and heated with a magnetic stirrer until the dispersion temperature was 80°C, 85°C, 90°C, and 95°C, respectively. The TPU parts were evenly rolled with a roller and dried in a convection oven for 12 hours to prepare a CNTs-COOH / TPU composite material.
[0063] The strain tensile image and resistivity image of the CNTs-COOH / TPU composite material prepared in this example are as follows: Figure 2 shown.
[0064] Step 4: Preparation of Zr / CNTs-COOH / TPU,
[0065] Add 2g C6H8O7, 50mL deionized water, and 0.6% Zr(SO4)2 by mass of TPU to prepare an acid bath with a pH value of 2.5. Add the CNTs-COOH / TPU composite material to the Zr(SO4)2 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to prepare the Zr / CNTs-COOH / TPU composite material.
[0066] Step 5: Surface hydrophobicity treatment of Zr / CNTs-COOH / TPU composite material.
[0067] The concentration of the PDMS-modified polyurethane emulsion was diluted to 5wt%, and the spin spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, the shaker was operated at 200 rpm / min for 30 min, and the convection oven was dried for 4 h to prepare a hydrophobic Zr / CNTs-COOH / TPU composite material, that is, a 3D printed TPU-based composite material.
[0068] Example 3
[0069] This example provides a TPU-based composite material and a preparation method thereof.
[0070] The materials used in this embodiment are TPU, CNTs, H2SO4, HNO3, C6H8O7, Zr(SO4)2, and deionized water.
[0071] Step 1: Prepare TPU parts.
[0072] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0073] Step 2: Prepare CNTs-COOH dispersion,
[0074] (1) Using CNTs as raw materials, placing CNTs in a ball mill and milling them at a speed of 200 pm / min for 60 min;
[0075] (2) H2SO4 and HNO3 were mixed in a volume ratio of 3:1, and CNTs were dispersed in the acid mixed solution, and ultrasonic dispersion was performed at a power of 300 W for 60 min, and mechanical stirring was performed at a speed of 300 rpm / min at room temperature for 20 min to obtain a CNTs mixed solution;
[0076] (3) taking the CNTs mixed solution and filtering it, washing the filtered product with deionized water three times, and drying it in a vacuum oven at 60° C. for 12 h to obtain CNTs-COOH;
[0077] (4) Take CNTs-COOH, add deionized water, prepare a CNTs-COOH solution with a solid content of 10%, and perform ultrasonic dispersion treatment at a power of 300 W for 60 minutes to obtain a CNTs-COOH dispersion.
[0078] Step 3: Preparation of CNTs-COOH / TPU,
[0079] (1) Diluting the solid content of the CNTs-COOH dispersion to 1%, taking 2%, 4%, 6%, 8%, and 10% of the mass of the TPU product, respectively, ultrasonically dispersed at a power of 300 W for 30 min, and mechanically stirred at a speed of 300 rpm / min for 20 min;
[0080] (2) A gradient heating low-temperature dyeing process was adopted with the following process conditions: bath ratio 1:20, heating rate 1°C / min, temperature rising from room temperature to 90°C, and holding time of 60 min after reaching the specified temperature of 90°C. CNTs-COOH and TPU parts were compounded by infrared dyeing machine, then washed with water, and dried in convection oven for 12 h to prepare CNTs-COOH / TPU composite materials.
[0081] The strain tensile image and resistivity image of the CNTs-COOH / TPU composite material prepared in this example are as follows: Figure 3 shown.
[0082] Step 4: Preparation of Zr / CNTs-COOH / TPU,
[0083] Add 2g C6H8O7, 50mL deionized water, and 0.6% Zr(SO4)2 by mass of TPU to prepare an acid bath with a pH value of 2.5. Add the CNTs-COOH / TPU composite material to the Zr(SO4)2 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to prepare the Zr / CNTs-COOH / TPU composite material.
[0084] Step 5: Surface hydrophobicity treatment of Zr / CNTs-COOH / TPU composite material.
[0085] The concentration of the PDMS-modified polyurethane emulsion was diluted to 5wt%, and the spin spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, the shaker was operated at 200 rpm / min for 30 min, and the convection oven was dried for 4 h to prepare a hydrophobic Zr / CNTs-COOH / TPU composite material, that is, a 3D printed TPU-based composite material.
[0086] Example 4
[0087] This example provides a TPU-based composite material and a preparation method thereof
[0088] The materials used in this embodiment are TPU, CNTs, H2SO4, HNO3, C6H8O7, Zr(SO4)2, and deionized water.
[0089] Step 1: Prepare 3D printed TPU parts.
[0090] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0091] Step 2: Prepare CNTs-COOH dispersion,
[0092] (1) Using CNTs as raw materials, placing CNTs in a ball mill and milling them at a speed of 200 pm / min for 60 min;
[0093] (2) H2SO4 and HNO3 were mixed in a volume ratio of 3:1, and CNTs were dispersed in the acid mixed solution, and ultrasonic dispersion was performed at a power of 300 W for 60 min, and mechanical stirring was performed at a speed of 300 rpm / min at room temperature for 20 min to obtain a CNTs mixed solution;
[0094] (3) taking the CNTs mixed solution and filtering it, washing the filtered product with deionized water three times, and drying it in a vacuum oven at 60° C. for 12 h to obtain CNTs-COOH;
[0095] (4) Take CNTs-COOH, add deionized water, prepare a CNTs-COOH solution with a solid content of 10%, and perform ultrasonic dispersion treatment at a power of 300 W for 60 minutes to obtain a CNTs-COOH dispersion.
[0096] Step 3: Preparation of CNTs / TPU,
[0097] (1) diluting the solid content of the CNTs-COOH dispersion to 1%, taking 8% of the mass of the TPU CNTs-COOH dispersion, ultrasonically dispersing at a power of 300 W for 30 min, and mechanically stirring at a speed of 300 rpm / min for 20 min;
[0098] (2) A gradient heating low-temperature dyeing process was adopted with the following process conditions: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time of 40 min after reaching the specified temperature of 90°C. CNTs-COOH and TPU parts were compounded by infrared dyeing machine, then washed with water, and dried in convection oven for 12 h to prepare CNTs-COOH / TPU composite materials.
[0099] Step 4: Preparation of Zr / CNTs-COOH / TPU,
[0100] Add 2g C6H8O7, 50mL deionized water, and Zr(SO4)2 with TPU masses of 0.2%, 0.4%, 0.6%, 0.8% and 1.0% respectively, prepare an acid bath with a pH value of 2.5, add CNTs-COOH / TPU composite material into the Zr(SO4)2 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to prepare Zr / CNTs-COOH / TPU composite material.
[0101] Step 5: Surface hydrophobicity treatment of Zr / CNTs-COOH / TPU composite material.
[0102] The concentration of the PDMS-modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, and the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties, thereby obtaining a TPU-based composite material.
[0103] The TPU-based composite material of this embodiment can be obtained according to the above steps.
[0104] Example 5
[0105] This example provides a TPU-based composite material and a preparation method thereof.
[0106] The materials used in this embodiment are TPU, CNTs, H2SO4, HNO3, C6H8O7, Zr(SO4)2, and deionized water.
[0107] Step 1: Prepare TPU parts.
[0108] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0109] Step 2: Prepare CNTs-COOH dispersion,
[0110] (1) Using CNTs as raw materials, placing CNTs in a ball mill and milling them at a speed of 200 pm / min for 60 min;
[0111] (2) H2SO4 and HNO3 were mixed in a volume ratio of 3:1, and CNTs were dispersed in the acid mixed solution, and ultrasonic dispersion was performed at a power of 300 W for 60 min, and mechanical stirring was performed at a speed of 300 rpm / min at room temperature for 20 min to obtain a CNTs mixed solution;
[0112] (3) taking the CNTs mixed solution and filtering it, washing the filtered product with deionized water three times, and drying it in a vacuum oven at 60° C. for 12 h to obtain CNTs-COOH;
[0113] (4) Take CNTs-COOH, add deionized water, prepare a CNTs-COOH solution with a solid content of 10%, and perform ultrasonic dispersion treatment at a power of 300 W for 60 minutes to obtain a CNTs-COOH dispersion.
[0114] Step 3: Preparation of CNTs-COOH / TPU,
[0115] (1) diluting the solid content of the CNTs-COOH dispersion to 1%, taking 8% of the mass of the TPU CNTs-COOH dispersion, ultrasonically dispersing at a power of 300 W for 30 min, and mechanically stirring at a speed of 300 rpm / min for 20 min;
[0116] (2) A gradient heating low-temperature dyeing process was adopted with the following process conditions: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time for 40 min after reaching the specified temperature of 90°C. The CNTs-COOH and TPU parts were compounded by an infrared dyeing machine, then washed with water, and dried in a convection oven for 12 h to prepare a CNTs-COOH / TPU composite material.
[0117] Step 4: Preparation of Zr / CNTs-COOH / TPU,
[0118] Add 5g, 4g, 1g, 0.5g, 0.1g C6H8O7, 50mL deionized water and 0.6% Zr(SO4)2 by mass of TPU respectively, prepare acid baths with pH values of 2, 2.5, 3, 3.5, and 4 respectively, add CNTs-COOH / TPU composite material into the Zr(SO4)2 acid bath, stir mechanically at 100rpm / min for 10min, dry in convection oven for 12h, and prepare Zr / CNTs-COOH / TPU composite material.
[0119] Step 5: Surface hydrophobicity treatment of Zr / CNTs-COOH / TPU composite material.
[0120] The concentration of the PDMS-modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, and the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties, thereby obtaining a TPU-based composite material.
[0121] The TPU-based composite material of this embodiment can be obtained according to the above steps.
[0122] The strain tensile image and resistivity image of the Zr / CNTs-COOH / TPU composite material prepared in this example are shown in FIG. Figure 7 shown.
[0123] Example 6
[0124] This example provides a TPU-based composite material and a preparation method thereof.
[0125] The materials used in this embodiment are TPU, CNTs, H2SO4, HNO3, C6H8O7, Zr(SO4)2, and deionized water.
[0126] Step 1: Prepare TPU parts.
[0127] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0128] Step 2: Prepare CNTs-COOH dispersion,
[0129] (1) Using CNTs as raw materials, placing CNTs in a ball mill and milling them at a speed of 200 pm / min for 60 min;
[0130] (2) H2SO4 and HNO3 were mixed in a volume ratio of 3:1, and CNTs were dispersed in the acid mixed solution, and ultrasonic dispersion was performed at a power of 300 W for 60 min, and mechanical stirring was performed at a speed of 300 rpm / min at room temperature for 20 min to obtain a CNTs mixed solution;
[0131] (3) taking the CNTs mixed solution and filtering it, washing the filtered product with deionized water three times, and drying it in a vacuum oven at 60° C. for 12 h to obtain CNTs-COOH;
[0132] (4) Take CNTs-COOH, add deionized water, prepare a CNTs-COOH solution with a solid content of 10%, and perform ultrasonic dispersion treatment at a power of 300 W for 60 minutes to obtain a CNTs-COOH dispersion.
[0133] Step 3: Preparation of CNTs-COOH / TPU,
[0134] (1) diluting the solid content of the CNTs-COOH dispersion to 1%, taking 8% of the mass of the TPU CNTs-COOH dispersion, ultrasonically dispersing at a power of 300 W for 30 min, and mechanically stirring at a speed of 300 rpm / min for 20 min;
[0135] (2) A gradient heating low-temperature dyeing process was adopted with the following process conditions: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time of 40 min after reaching the specified temperature of 90°C. The CNTs-COOH and TPU parts were compounded by an infrared dyeing machine, then washed with water, and dried in a convection oven for 12 h to obtain a CNTs-COOH / TPU composite material.
[0136] Step 4: Preparation of Zr / CNTs-COOH / TPU,
[0137] Add 2g C6H8O7, 50mL deionized water, and 0.6% Zr(SO4)2 by mass of TPU to prepare an acid bath with a pH value of 2.5. Add the CNTs / TPU composite material to the Zr(SO4)2 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to prepare the Zr / CNTs-COOH / TPU composite material.
[0138] Step 5: Surface hydrophobicity treatment of Zr / CNTs-COOH / TPU composite material
[0139] The concentration of the PDMS-modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties, and a TPU-based composite material was obtained.
[0140] The ultra-depth-of-field microscope image of the CNTs-COOH / TPU composite material prepared in this example is as follows: Figure 4 The scanning electron microscope image of the 3D printed TPU part is as follows: Figure 5 As shown; the scanning electron microscope image of the prepared Zr / CNTs-COOH / TPU composite material is shown Figure 6 As shown; the sensor images of the prepared CNTs-COOH / TPU and Zr / CNTs-COOH / TPU composite materials are shown Figure 8 The water contact angle test of the TPU-based composite material prepared in this embodiment is shown in Fig. 9 shown.
[0141] Example 7
[0142] This example provides a TPU-based composite material and a preparation method thereof.
[0143] The materials used in this example are TPU, Gr, H2 S O4, NaNO3, KMnO4, H2O2, HCl, C6H8O7, Al2(SO4)3, deionized water.
[0144] Step 1: Prepare TPU parts.
[0145] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0146] Step 2: Prepare GO dispersion.
[0147] Add 98% H2SO4 into a 500mL reaction bottle in an ice water bath, mix natural expanded graphite powder and NaNO3 in a mass ratio of 2:1 under stirring, and keep the reaction at about 4°C for 1h;
[0148] Then add appropriate amount of KMnO4 in batches, control the reaction temperature not exceeding 20°C, and react for 2h under stirring (the color changes from black to dark green);
[0149] Heat to about 35°C, react for 2 h under stirring, then slowly add 100 mL of deionized water, continue stirring for 30 min (the reaction solution turns khaki), then add 100 mL of deionized water to dilute, continue reacting for 2 h, finally cool to room temperature, and continuously add H2O2 to remove the residual oxidant until the solution turns bright yellow;
[0150] (4) Filter while hot and wash with 5% dilute HCl solution and deionized water until there is no -SO4 in the filtrate 2- Finally, the filter cake was ultrasonically dispersed in deionized water at 300 W for 60 min to obtain a GO aqueous dispersion.
[0151] Step 3: Preparation of GO / TPU,
[0152] (1) Dilute the solid content of GO dispersion to 1%, take GO dispersion with a mass content of 8% of TPU, and perform ultrasonic dispersion at a power of 300 W for 30 min and mechanical stirring at a speed of 300 rpm / min for 20 min;
[0153] (2) A gradient heating low-temperature dyeing process was adopted with the following process conditions: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time for 40 min after reaching the specified temperature of 90°C. GO and TPU parts were compounded by an infrared dyeing machine, then washed with water, and dried in a convection oven for 12 h to obtain a GO / TPU composite material.
[0154] Step 4: Preparation of Al / GO / TPU,
[0155] Add 1g C6H8O7, 50mL deionized water, and 0.6% Al2(SO4)3 by mass of TPU to prepare an acid bath with a pH value of 3. Add the GO / TPU composite material to the Al2(SO4)3 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to obtain the Al / GO / TPU composite material.
[0156] Step 5: Surface hydrophobicity treatment of Al / GO / TPU composite material.
[0157] The concentration of the HTPDMS-modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, and the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties, thereby obtaining a TPU-based composite material.
[0158] The TPU-based composite material prepared in this embodiment is a composite material in which the surface of the Al / GO / TPU composite material is treated to be hydrophobic.
[0159] Example 8
[0160] This example provides a TPU-based composite material and a preparation method thereof.
[0161] The materials used in this embodiment are TPU, Mxene, LiF, HCl, Ti3AlC2, N2, FeCl3, and deionized water.
[0162] Step 1: Prepare TPU parts.
[0163] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0164] Step 2: Prepare Mxene dispersion,
[0165] Dissolve 2 g of lithium fluoride in 20 mL of 9 mol / L HCl solution and stir in an ice bath;
[0166] Add 6% Ti3AlC2 of the mass of TPU, stir evenly and place in a 40℃ oil bath for etching for 48h. After etching, centrifuge the solution and collect the precipitate, add 0.1mol / L HCl solution for acid washing, wash with deionized water, and collect the precipitate by centrifugation;
[0167] The precipitate was added to deionized water, transferred to a gas washing bottle, connected to a N2 gas source for bubbling, and ultrasonically dispersed at 300W for 2h;
[0168] The solution is centrifuged and the upper liquid is collected to obtain the Mxene solution;
[0169] The obtained MXene solution was added with deionized water, ultrasonically dispersed for 60 min at a power of 300 W, and mechanically stirred at a speed of 300 rpm / min for 30 min to obtain a MXene dispersion.
[0170] Step 3: Preparation of MXene / TPU,
[0171] (1) diluting the solid content of the MXene dispersion to 1%, taking a dispersion of MXene with a mass content of 8% of TPU, ultrasonically dispersing at a power of 300 W for 30 min, and mechanically stirring at a speed of 300 rpm / min for 20 min;
[0172] (2) A gradient heating low-temperature dyeing process was adopted, and the process conditions were as follows: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time for 40 minutes after reaching the specified temperature of 90°C. The Mxene and TPU parts were compounded by an infrared dyeing machine, then washed with water, and dried in a convection oven for 12 hours to obtain a Mxene / TPU composite material.
[0173] Step 4: Preparation of Fe / Mxene / TPU,
[0174] Add 1g C6H8O7, 50mL deionized water, C6H8O7, deionized water, and 0.6% FeCl3 by mass of TPU to prepare an acid bath with a pH value of 3, add the Mxene / TPU composite material to the FeCl3 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to obtain a Fe / Mxene / TPU composite material.
[0175] Step 5: Fe / Mxene / TPU surface hydrophobic treatment,
[0176] The concentration of the HTPDMS-modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, and the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties, thereby obtaining a TPU-based composite material.
[0177] The TPU-based composite material prepared in this embodiment is a composite material of Fe / Mxene / TPU with its surface treated to be hydrophobic.
[0178] Example 9
[0179] This example provides a TPU-based composite material and a preparation method thereof.
[0180] The materials used in this embodiment are TPU, Mxene, LiF, HCl, Ti3AlC2, N2, Ce2(SO4)3, and deionized water.
[0181] Step 1: Prepare TPU parts.
[0182] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0183] Step 2: Prepare Mxene dispersion,
[0184] Dissolve 2 g of lithium fluoride in 20 mL of 9 mol / L HCl solution and stir in an ice bath;
[0185] Add 6% Ti3AlC2 of the mass of TPU, stir evenly and place in a 40℃ oil bath for etching for 48h. After etching, centrifuge the solution and collect the precipitate, add 0.1mol / L HCl solution for acid washing, wash with deionized water, and collect the precipitate by centrifugation;
[0186] The precipitate was added to deionized water, transferred to a gas washing bottle, connected to a N2 gas source for bubbling, and ultrasonically dispersed at 300W for 2h;
[0187] The solution is centrifuged and the upper liquid is collected to obtain the Mxene solution;
[0188] The obtained Mxene solution was added with deionized water, and ultrasonically dispersed for 60 min at a power of 300 W and mechanically stirred at a speed of 300 rpm / min for 30 min to obtain a Mxene dispersion.
[0189] Step 3: Preparation of Mxene / TPU,
[0190] (1) diluting the solid content of the MXene dispersion to 1%, taking a dispersion of MXene with a mass content of 8% of TPU, ultrasonically dispersing at a power of 300 W for 30 min, and mechanically stirring at a speed of 300 rpm / min for 20 min;
[0191] (2) A gradient heating low-temperature dyeing process was adopted, and the process conditions were as follows: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time for 40 minutes after reaching the specified temperature of 90°C. The Mxene and TPU parts were compounded by an infrared dyeing machine, then washed with water, and dried in a convection oven for 12 hours to obtain a Mxene / TPU composite material.
[0192] Step 4: Preparation of Ce / Mxene / TPU,
[0193] Add 2g C6H8O7, 50mL deionized water, and 0.6% Ce2(SO4)3 by mass of TPU to prepare an acid bath with a pH value of 2.5. Add the MXene / TPU composite material to the Ce2(SO4)3 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to obtain the Ce / MXene / TPU composite material.
[0194] Step 5: Surface hydrophobicity treatment of Ce / Mxene / TPU composite material.
[0195] The concentration of the HTPDMS-modified polyurethane emulsion was diluted to 5 wt %, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, the temperature was 20°C, the shaker was operated at 200 rpm / min for 30 min, and the convection oven was dried for 4 h to give the composite material hydrophobic properties, thereby obtaining a TPU-based composite material.
[0196] The TPU-based composite material prepared in this embodiment is a composite material of Ce / Mxene / TPU with its surface treated to be hydrophobic.
[0197] Example 10
[0198] This example provides a TPU-based composite material and a preparation method thereof.
[0199] The materials used in this embodiment are TPU, Mxene, LiF, HCl, Ti3AlC2, N2, LaCl3, and deionized water.
[0200] Step 1: Prepare TPU parts.
[0201] Using TPU as raw material, FDM 3D printing technology is used to prepare TPU parts.
[0202] Step 2: Prepare Mxene dispersion,
[0203] Dissolve 2 g of lithium fluoride in 20 mL of 9 mol / L HCl solution and stir in an ice bath.
[0204] Add 6% Ti3AlC2 of the mass of TPU, stir evenly and place in a 40°C oil bath for etching for 48 hours. After etching, centrifuge the solution and collect the precipitate, add 0.1 mol / L HCl solution for acid washing, wash with deionized water, and collect the precipitate by centrifugation.
[0205] The precipitate was added into deionized water, transferred into a gas washing bottle, connected to a N2 gas source for bubbling, and ultrasonically dispersed for 2 h at 300 W.
[0206] The above solution was centrifuged and the upper liquid was collected to obtain the Mxene solution.
[0207] The obtained Mxene solution was added with deionized water, and ultrasonically dispersed for 60 min at a power of 300 W and mechanically stirred at a speed of 300 rpm / min for 30 min to obtain a Mxene dispersion.
[0208] Step 3: Preparation of Mxene / TPU,
[0209] (1) Dilute the solid content of the Mxene dispersion to 1%, take a dispersion of Mxene with a mass content of 8% of TPU, and perform ultrasonic dispersion at a power of 300 W for 30 min and mechanical stirring at a speed of 300 rpm / min for 20 min.
[0210] (2) A gradient heating low-temperature dyeing process was adopted, and the process conditions were as follows: bath ratio 1:20, heating rate 2°C / min, temperature rising from room temperature to 90°C, and holding time for 40 minutes after reaching the specified temperature of 90°C. The Mxene and TPU parts were compounded by an infrared dyeing machine, then washed with water, and dried in a convection oven for 12 hours to prepare a Mxene / TPU composite material.
[0211] Step 4: Preparation of La / Mxene / TPU,
[0212] Add 1g C6H8O7, 50mL deionized water, and 0.6% LaCl3 by mass of TPU to prepare an acid bath with a pH value of 3. Add the Mxene / TPU composite material to the LaCl3 acid bath, stir mechanically at 100rpm / min for 10min, and dry in a convection oven for 12h to obtain a La / Mxene / TPU composite material.
[0213] Step 5: La / Mxene / TPU surface hydrophobic treatment,
[0214] The concentration of the HTPDMS modified polyurethane emulsion was diluted to 5wt%, and the rotary spraying operation was repeated three times. The composite material obtained in step 4 was placed in a conical flask, and the temperature was 20°C, and the shaker was operated at 200 rpm / min for 30 minutes, and the convection oven was dried for 4 hours to give the composite material hydrophobic properties. Thus, a TPU-based composite material was obtained.
[0215] The TPU-based composite material prepared in this embodiment is a composite material of La / Mxene / TPU with its surface treated to be hydrophobic.
[0216] Embodiment 11
[0217] This example is a performance test of TPU-based composite materials and their intermediate products
[0218] This example tests the performance of the composite materials and their intermediate products prepared under different conditions. The mechanical properties of the composite materials were analyzed using a universal tensile testing machine; the conductivity was analyzed using a four-probe resistivity tester; the sensing performance was analyzed using an electrochemical workstation, and the sensing performance was determined by observing the change amplitude of the composite materials under bending at different angles of 30°, 90°, and 150°. The CNTs dispersion was tested using scanning electron microscope images and 3D images. The performance test results are as follows:
[0219] (1) Test results of electrical conductivity and mechanical properties
[0220] The intermediate product CNTs-COOH / TPU of the TPU-based composite material prepared in Example 1 was tested for mechanical properties and electrical conductivity. The mechanical properties test results are as follows: Figure 1 As shown in (a): The composite material of CNTs and TPU with 8% TPU mass has almost no effect on the overall strain tensile properties of CNTs-COOH / TPU composite materials compared with TPU parts formed by 3D printing under different temperature gradients. The results show that the addition of CNTs within a specific temperature range has a low sensitivity to the mechanical properties of CNTs-COOH / TPU composite materials, indicating that CNTs and TPU parts are firmly combined and have good mechanical properties. The conductivity test results are shown in Figure 1 (b) shows that the resistivity of the composite material of CNTs-COOH / TPU with a TPU mass ratio of 8% reaches 75.2Ω·cm at a specific temperature of 90°C, indicating that the CNTs-COOH / TPU composite material exhibits good conductive properties.
[0221] The intermediate product CNTs-COOH / TPU of the TPU-based composite material prepared in Example 2 was tested for mechanical properties and electrical conductivity. The mechanical properties test results are as follows: Figure 2 As shown in (a): The composite material of CNTs and TPU with 8% TPU mass has almost no effect on the overall strain tensile properties of CNTs-COOH / TPU composite materials compared with TPU parts formed by 3D printing under different temperature gradients. The results show that the addition of CNTs within a specific temperature range has a low sensitivity to the mechanical properties of CNTs-COOH / TPU composite materials, indicating that CNTs and TPU parts are firmly combined and have good mechanical properties. The conductivity test results are shown in Figure 2 (b) shows that the resistivity of the composite material of CNTs-COOH / TPU with a TPU mass ratio of 8% reaches 246.46Ω·cm at a specific temperature of 90°C, indicating that the CNTs-COOH / TPU composite material exhibits relatively good conductive properties.
[0222] Example 1 uses a gradient temperature rise process to prepare the TPU composite material, and Example 2 uses a conventional process to prepare the TPU composite material. Data comparison shows that the mechanical properties of the CNTs-COOH / TPU composite materials prepared by the two processes are not much different, but the conductivity of the CNTs-COOH / TPU composite material prepared by the gradient temperature rise process is significantly improved compared with the conventional process.
[0223] The mechanical properties and electrical conductivity of the intermediate product CNTs-COOH / TPU of the TPU-based composite material prepared in Example 3 were tested. The mechanical properties test results are as follows: Figure 3 (a) shows the mechanical properties of composite materials of TPU and different amounts of CNTs at a temperature of 90°C. Compared with TPU parts formed by 3D printing, the overall strain tensile properties of CNTs-COOH / TPU composite materials are almost unaffected by different amounts of CNTs. The results show that the addition of CNTs and the change of temperature within a specific range have a low sensitivity to the mechanical properties of the composite material, indicating that CNTs are firmly bonded to TPU parts and have good mechanical properties. The conductivity test results are shown in Figure 3 (b) shows the conductive properties of CNTs-COOH / TPU composites with different CNTs dosages at 90°C. From the data in the figure, it can be clearly observed that when the amount of CNTs is 8% of the mass of TPU, the resistivity of the CNTs-COOH / TPU composite material is significantly reduced to 75.2Ω·cm. This result shows that the CNTs-COOH / TPU composite material exhibits good conductive properties.
[0224] The mechanical properties and electrical conductivity of the TPU-based composite material Zr / CNTs-COOH / TPU prepared in Example 5 were tested. The mechanical properties test results are shown in Figure 7 (a) shows the mechanical properties of the composite material at 90°C, 8% CNTs by mass of TPU, and 0.6% Zr(SO4)2 by mass of TPU in acid baths with different pH values. Compared with the intermediate product CNTs-COOH / TPU prepared in Example 1 and Example 3, the strain tensile properties are almost unchanged. The results show that the introduction of transition metal ions also shows that the composite material has good mechanical properties. The test results of the electrical conductivity are shown in Figure 7 (b) shows the conductivity of the composite material at 90°C, 8% CNTs by mass of TPU, and 0.6% Zr(SO4)2 by mass of TPU in acidic baths with different pH values. Compared with the intermediate product CNTs-COOH / TPU prepared in Example 1 and Example 3, the conductivity is improved. The results show that the introduction of transition metal ions makes the composite material have better conductivity.
[0225] (2) CNTs dispersion test results
[0226] The ultra-depth-of-field microscope image of the intermediate product CNTs-COOH / TPU of the TPU-based composite material prepared in Example 6 is as follows: Figure 4 As shown. Figure 4 As shown in (a), CNTs-COOH is evenly distributed on the surface of CNTs-COOH / TPU composites; Figure 4 (b) shows the 3D image of the CNTs-COOH / TPU composite material. CNTs-COOH is evenly distributed in TPU parts with different thicknesses. SEM images of 3D printed TPU parts at different magnifications are shown in Figure 2. Figure 5 As shown; SEM images of the TPU-based composite intermediate product CNTs-COOH / TPU prepared in Example 6 at different magnifications, such as Figure 6 As shown, it can be seen that CNTs are dispersed more evenly in the 3D printed TPU parts.
[0227] (3) Sensing performance test results
[0228] The TPU-based composite material prepared in Example 6 was tested for sensing performance. The results of the sensing performance test are as follows: Figure 8 As shown in (a), the sensitivity of CNTs-COOH / TPU composite material at bending angles of 30°, 90°, and 150° corresponds to approximately 40%, 50%, and 60%, respectively; Figure 8 As shown in (b), the Zr / CNTs-COOH / TPU composite material has a sensitivity of approximately 70%, 90%, and 120% at bending angles of 30°, 90°, and 150°, respectively, indicating that the composite material has good sensing performance. At the same time, the introduction of transition metal ions improves the sensing performance of the composite material.
[0229] The hydrophobicity test results of the TPU-based composite material prepared in Example 6 are as follows: Fig. 9 As shown in (a), the water contact angle of the 3D printed TPU-based composite material reaches 138.8°; Fig. 9 As shown in (b), the water contact angle of the 3D printed TPU-based composite material reaches 141.5°, which shows excellent hydrophobic properties. This is because CNTs and hydrophobic materials work together on the surface of TPU parts, including reducing surface energy, enhancing interlayer bonding and producing synergistic effects. These effects work together on the surface of the composite material, giving it excellent hydrophobic properties and a long service life. Among them, the different water contact angles are due to differences in the sample surfaces, resulting in small differences in the water contact angle test results; at the same time, after the composite material is hydrophobicized, it has little effect on the conductive and sensing properties.
[0230] As described above, the present invention can be well implemented. The above embodiments are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various changes and improvements made to the technical solutions of the present invention by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for preparing a TPU-based composite material, characterized in that: include: The dispersion containing the nano-conductive material is mixed with the TPU product, and the mixture is subjected to a temperature-raising dyeing treatment, an acid bath treatment and a surface hydrophobicity treatment in sequence to obtain the TPU-based composite material; The temperature-raising dyeing treatment is from room temperature to 80° C. to 95° C., the heating rate is 1 to 2° C. / min, and the heat preservation time is 40 to 60 min.
2. The method for preparing the TPU-based composite material according to claim 1, characterized in that: The nano conductive material is a mixture of one or more of carbon nanotubes, graphene and Mxene.
3. The method for preparing the TPU-based composite material according to claim 1, characterized in that: The TPU component is made of TPU as raw material by adopting fused deposition modeling 3D printing technology.
4. The method for preparing the TPU-based composite material according to claim 1, characterized in that: In terms of mass percentage, the nano conductive material accounts for 2% to 10% of the TPU component.
5. The method for preparing the TPU-based composite material according to claim 1, characterized in that: Before the dispersion containing the nano-conductive material is compounded with the TPU product, the dispersion is subjected to ultrasonic and / or mechanical stirring; The dispersion of the nano-conductive material is optimized by ultrasonic and mechanical stirring.
6. The method for preparing the TPU-based composite material according to claim 1, characterized in that: The salt compound used in the acid bath treatment is selected from at least one of Zr(SO4)2, Al2(SO4)3, FeCl3, Ce2(SO4)3, and LaCl3; The pH value of the acid bath treatment is 2-4.
7. The method for preparing the TPU-based composite material according to claim 1, characterized in that: The surface hydrophobic treatment material used in the surface hydrophobic treatment is polydimethylsiloxane-modified polyurethane and / or hydroxyl-terminated polydimethylsiloxane-modified polyurethane.
8. The method for preparing the TPU-based composite material according to claim 7, characterized in that: In terms of mass percentage, the concentration of the surface hydrophobic treatment material is 2% to 5%.
9. A TPU-based composite material, characterized in that: The composite material is prepared by the method for preparing the TPU-based composite material according to any one of claims 1 to 8.
10. Use of the TPU-based composite material according to claim 9 in preparing wearable electronic devices.
Citation Information
Patent Citations
Preparation method and application of durable sensing antibacterial composite fabric and strain sensor
CN115058898A
CNTs / rGO / TPU flexible material and preparation method thereof
CN115216137A
Preparation method of strain / humidity sensing material with hydrophobic surface
CN115979112A
Conductive TPU film and manufacturing method therefor
WO2022036982A1